Correction: A Δ-machine learning approach for force fields, illustrated by a CCSD(T) 4-body correction to the MB-pol water potential. (25th October 2022) - Qu, Chen; Yu, Qi; Conte, Riccardo; Houston, Paul L.; Nandi, Apurba; Bowman, Joel M.
Abstract : Correction for 'A Δ-machine learning approach for force fields, illustrated by a CCSD(T) 4-body correction to the MB-pol water potential' by Chen Qu et al., Digital Discovery, 2022, 1, 658–664, ; https://doi.org/10.1039/D2DD00057A .